Inflation dynamics and dual inflation in accession countries: a 'New Keynesian' perspective - Olga Arratibel; Diego Rodriguez-Palenzuela; Christian Thimann (European Central Bank (ECB), 2002)
This paper examines inflation dynamics in the current EU-accession countries in central and eastern Europe, focusing particularly on the determinants of 'dual inflation', that is, diverging inflation rates for tradable and non-tradable goods. The paper draws on the recently published data for the Harmonized Index of Consumer Prices (HICP) of the Accession countries and, indeed, finds evidence of ' dual inflation' in these economies. To test empirically for underlying determinants, the paper borrows from the recently developed New Phillips curve literature. Overall, domestic factors have systematically a stronger impact upon non-tradable goods inflation whereas international factors have a stronger impact over tradable goods. Furthermore, the results point to the possibly very different effects of exchange rate regimes over tradable and non-tradable goods inflation. On the whole, the findings suggest that the Balassa-Samuelson effect is not a prominent factor behind the current 'experience' of dual inflation in these countries.
Keywords: E31; E58; F41; P24; 330